Research Trends and Gaps in Renewable Energy Learning Based on Local Potential in Science Education: A Systematic Literature Review - Yufi Nugroho; Arif Widiyatmoko; Sudarmin; Novi Ratna Dewi; Haniza Hanim bt Mohd Zain (Universitas Syiah Kuala, in collaboration with the Perkumpulan Pendidik IPA Indonesia (PPII), (MoU), 2026)
The renewable energy transition is a crucial global issue, but science learning in schools is often abstract and disconnected from the context of the students' real environment. This research aims to map research trends and identify gaps in renewable energy learning based on local potential through systematic literature review (SLR). Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol, a total of 12 high-quality articles from the 2021-2025 period were comprehensively analyzed. The results of the synthesis show a paradigm shift towards place-based education (PBE) and the food-energy-water nexus system which is strengthened by the integration of artificial intelligence (AI) technology to track students' learning trajectories in a non-linear manner. However, significant gaps were found in the form of the dominance of textbook content that is still theoretical-cognitive and the lack of synchronization between curriculum policies and the use of unique regional resources. In conclusion, this study offers the adaptive local learning model as a strategic bridge to transform energy education to be more socioculturally responsive and sustainable. These findings contribute a systematic and evidence-based understanding to the development of science curricula rooted in the power of local communities